[Life in the camp ; Zero waste ; Kenkoy loves Rosing [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1991)
The problems of Aeta refugees from Mt. Pinatubo eruption continues to mount as disease, death no potable water and no shelter. Recycling garbage makes money. Regine and Janno star in this Pinoy musicale about a boy meeting a girl and falling in love. Kenkoy the comic strip character, caricatures the dream to seek greener pastures in America.
Life in the camp (14 min.) -- Zero waste (16 min.) -- Kenkoy loves Rosing (16 min.)
VHS.
Keywords: Recycling (Waste, etc.) -- Philippines; Children's plays -- Presentation, etc; Musical theater -- Philippines; Refuse and refuse disposal -- Philippines -- San Juan (Manila)